PEMEROLEHAN NOMINA FAUNA BAHASA DAYAK KANAYATN ANAK USIA 6 TAHUN DI DESA PENDARING NYARUMKOP - Ersa, Olyvia Gloria; Simanjuntak, Hotma; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This research was motivated by the researcher's curiosity regarding the acquisition of Dayak Kanayatn language fauna nouns by 6 year old children in Pendaring Nyarumkop Village. Aims to describe the acquisition of Dayak Kanayatn language fauna nouns aged 6 years in Pendaring Nyarumkop Village, and implementation in Indonesian language learning. The research data sources consist of four, namely Diana Kartika, Apriliani, Digo Pratama, and Purnama Yordan. The form of research used is qualitative with descriptive methods. Data collection tools are gadgets, question lists, picture lists, and notetaking sheets. Data collection techniques are face-to-face techniques, interviews, recording and note-taking, and documentation. The technique for testing the validity of the data is the persistence of observations and the adequacy of references. The results of the research show that first, Diana Kartika obtained 34 data on fauna nouns in the Dayak Kanayatn language in the form of monomorphemics totaling 33 nouns and phrases totaling 1 noun. Second, Apriliani obtained 35 data on fauna nouns in the Dayak Kanayatn language in the form of monomorphemics totaling 31 nouns and phrases totaling 4 nouns. Third, Digo Pratama obtained 39 data on fauna nouns in the Dayak Kanayatn language in the form of monomorphemics totaling 37 nouns and phrases totaling 2 nouns. Fourth, Purnama Yordan obtained 37 data on fauna nouns in the form of monomorphemics totaling 35 nouns and phrases totaling 2nouns. The factors that influence language acquisition are biology, social environment, intelligence, and motivation.